Use of contrast-enhanced ultrasonography in chronic pathologic canine testes - Volta, A.; Manfredi, S.; Vignoli, M.; Russo, M.; England, G.C.W.; Rossi, F.; Bigliardi, E.; Di Ianni, F.; Parmigiani, E.; Bresciani, C.; Gnudi, G. (Wiley, 2014)
Contrast-enhanced ultrasound with sulphur hexafluoride microbubbles was performed in seven healthy dogs without a history of reproductive pathology and with histologically confirmed normal testes and in 42 dogs with chronic scrotal anomalies. All dogs underwent orchiectomy and histological examination. Enhancement patterns and perfusion parameters (peak intensity and regional blood flow) of testes of healthy dogs and testes with chronic lesions were compared. Fourteen non-pathologic and 60 pathologic testes were considered. Forty testes were neoplastic (24 interstitial cell tumours, 9 seminomas, 7 Sertoli cell tumours), 20 were non-neoplastic (16 testicular degenerations, 2 chronic orchitis, 1 testicular atrophy, 1 interstitial cell hyperplasia). In healthy dogs, the contrast medium flow had a rapid homogeneous wash-in and wash-out, with a short peak phase. With contrast ultrasound, testes that were inhomogeneous with a hyperenhancing pattern were associated with neoplasia (sensitivity: 87.5%, specificity: 100%). Lesions with persistent inner vessels and a hypoto-isoechoic background were significantly associated with seminomas (sensitivity: 77.8%, specificity: 100%). Testes with non-neoplastic lesions were characterized by a scant/moderate homogeneous enhancement. Perfusion parameters were higher in neoplastic lesions. Contrast ultrasound was a feasible diagnostic tool in the assessment of testicular lesions, with hyperenhancement being an important feature in the diagnosis of malignancy.